A review on airport gate assignment problems: Single versus multi objective approaches. (April 2020) - Daş, Gülesin Sena; Gzara, Fatma; Stützle, Thomas
Highlights: Past work on Gate Assigment Problems (GAP) are reviewed with a focus on identifying types of formulations, classifying objectives, and categorising solution methods. There is no standard formulation of the problem. Passenger oriented objectives are most common. Recent work on GAP are multi-objective. In terms of solution methods, heuristic and metaheuristic approaches are dominant. Abstract: Assigning aircraft to gates is an important decision problem that airport professionals face every day. The solution of this problem has raised a significant research effort and many variants of this problem have been studied. In this paper, we review past work with a focus on identifying types of formulations, classifying objectives, and categorising solution methods. The review indicates that there is no standard formulation, that passenger oriented objectives are most common, and that more recent work are multi-objective. In terms of solution methods, heuristic and metaheuristic approaches are dominant which provides an opportunity to develop exact and approximate approaches both for the single and multi-objective problems.